Increasing Learning Outcomes in Creative Dance Works Through the Project Based Learning Video - Haryanti Haryanti (Indonesian Journal of Multidisciplinary Science, 2021)
This study aims to determine the implementation of the act of learning to create creative dances through the right model can improve student learning outcomes for Class XI MIPA 4 SMA Negeri 1 Banguntapan in the 2019/2020 school year. The population in this study were all students of Class XI SMA Negeri 1 Banguntapan and as a sample were students of Class XI MIPA 4, totaling 31 students. Collecting data using student learning outcomes tests and observations to measure the accuracy of the action. Data analysis in this study used quantitative and qualitative description techniques. The results of this study are the implementation of learning actions for creative dance work through the Project Based Learning model can improve student learning outcomes for class XI MIPA 4 SMA Negeri 1 Banguntapan in the 2019/2020 school year.